2020
DOI: 10.47772/ijriss.2020.41201
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition, Board Size and Market Value of Listed Industrial Goods Companies in Nigeria

Abstract: This study examines the impact of board composition and board size on the market value of listed industrial goods companies in Nigeria. Ex-post factor research design was used and data was collected from annual reports and account of the sampled companies for the period from 2010 to 2019. The ordinary least square, fixed and random effects regression techniques were applied on the panel data collated to estimate the models. The paper documents significant positive effect of board size on the market value of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Following the addition of board independence, our results displayed a significant positive correlation between leverage and firm performance as shown in the estimation results of Model 2. This corroborates with the previous empirical works by Abdulkarim and Bahamman (2021) and Ramli et al (2019), suggesting that higher gearing will enhance firms' profitability. The positive association is probable to the tendency of Malaysian firms to use external financing instead of internal financing to enhance their financial performance.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Following the addition of board independence, our results displayed a significant positive correlation between leverage and firm performance as shown in the estimation results of Model 2. This corroborates with the previous empirical works by Abdulkarim and Bahamman (2021) and Ramli et al (2019), suggesting that higher gearing will enhance firms' profitability. The positive association is probable to the tendency of Malaysian firms to use external financing instead of internal financing to enhance their financial performance.…”
Section: Resultssupporting
confidence: 92%
“…Results showed a significant negative moderating effect of board independence in the capital structure and firm performance relationship. It was observed that adding independent directors to the board has negatively changed the association between debt and firm performance, which is consistent with the empirical work of Abdulkarim and Bahamman (2021). In contrast to Mubaraq, Rahayu, Saifi, and Darmawan (2021), this study implies that increasing the control exercised by independent directors to reduce agency conflicts has an adverse impact on the relationship between debt and performance.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…‫اإلعالن‬ ‫أثر‬ ‫المالية‬ ‫السوق‬ ‫يستوعب‬ ‫بحيث‬ ‫مناسبة‬ ‫ة‬ ‫فتر‬ ‫تعد‬ ‫ة‬ ‫الفتر‬ ‫هذه‬ ‫أن‬ ‫الباحث‬ ‫ويرى‬ ‫الشركات.‬ ‫حوكمة‬ ‫آليات‬ ‫خصائص‬ ‫عن‬ ‫معلومات‬ ‫من‬ ‫يحتويه‬ ‫وما‬ ‫ة‬ ‫اإلدار‬ ‫مجلس‬ ‫ير‬ ‫تقر‬ ‫عن‬ Corrado, 2011;Lehmann & Schwerdtfeger, 2016;Rahman et al, 2021;Roca, 2013;Syed & Bajwa, 2018 Abdulkarim et al, 2020;Ahulu & MacCarthy, 2019;Al Farooque et al, 2020;Al Harbi, 2018;Assidi, 2020;Bansal & Sharma, 2016;Devi & Suardana, 2021;Dunstan et al, 2011;Fariha et al, 2021;Khalifa, 2018;Khanh et al, 2020;Syafitri, Ahulu & MacCarthy, 2019;Al Farooque et al, 2020;Assidi, 2020;Bhat et al, 2018;Chua & Ab Razak, 2018;Devi & Suardana, 2021;Dunstan et al, 2011;Gurusamy, 2017;Khalifa, 2018;Khan et al, 2017;Khanh et al, 2020 Ananzeh, I. N. (2021). investigating the efficiency of financial markets: empirical evidence from mena countries.…”
unclassified